PR practitioners’ roles in crisis management: Malaysian perspectives - Ahmad, Zeti Azreen; Syed Abdullah Idid, Syed Arabi (University of Newcastle, Australia, 2020)
Crisis refers to any occurrence that disturbs a normal routine of individuals or organisations and that inflicts undesirable consequences. Strategic management of a crisis is instrumental to lessen the undesirable impact to those affected. Over the years, scholars have developed theoretical frameworks and strategic responses to salvage organisations’ reputation from a myriad of crises. Major crises mainly in the United States and Europe, have been documented as case studies for teaching and learning. However, it is worth noting that there is no one-size-fits-all strategy in handling crises. Despite numerous crises events that have occurred in Malaysia, little attempt has been made to examine how these crises were managed from the public relations’ (PR) perspective. In addition, how PR practitioners in Malaysia perceived their role in crisis management and how they respond to a crisis have not been much explored. In view of this gap, this study aims to address the following objectives; (i) to explore how PR practitioners in Malaysia perceived their involvement in crisis management, (ii) to identify crisis response strategies adopted by practitioners and (iii) to examine possible role conflict perceived by PR practitioners in crisis management within an organisation. More than 300 PR practitioners working in various organizations in Malaysia took part in a survey conducted in 2018. The findings among others affirmed that PR practitioners perceived their role as dominant and important in crisis management. However, practitioners’ reactive approach in crisis management could hinder their ability in managing crisis effectively. The present study serves as a significant attempt to enrich the existing literature on PR role in crisis management from PR practitioners’perspective.